IDENTIFIKASI KUALITAS AUDIT PADA HUBUNGAN KOMPENSASI EKSEKUTIF DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK - Fitri Wulandari (2020)
This study aims to determine the effect of audit quality on the relationship of executive compensation and capital intensity on tax avoidance. In this study tax avoidance is proxied using Book Tax Differences (BTD). The sample used in this study were 97 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The analysis technique used in this study is panel data regression analysis with a significance level of 5% and using the STATA 13 application in testing hypotheses. The results in this study found that (1) executive compensation had no effect on tax avoidance. (2) capital intensity has a significant effect on tax avoidance. (3) audit quality does not weaken the relationship between executive compensation and tax avoidance. (4) audit quality does not strengthen the relationship of capital intensity to tax avoidance.